A taste of one’s own medicine: Bacillus velezensis isolated from adult housefly intestines demonstrates effective fly control - Li, Ying; Wang, Shumin; Yao, Dawei; Zhang, Kexin; Yin, Yansong; Kong, Xinxin; Li, Jinxiao; Zeng, Lingxia; Zhang, Ruiling; Zhang, Zhong (Frontiers in Immunology, 2025)
IntroductionBacillus spp. are widely used as biological agents for managing diseases in crops, livestock, poultry, and aquatic animals. Bacillus velezensis, a novel species within the Bacillus genus, is extensively used in the biological control of animal and plant diseases. However, the association between B. velezensis and insect hosts remains a complex and poorly understood process.MethodsIn this study, we utilized a housefly larvae model to investigate the relationship between B. velezensis and houseflies by examining the changes in intestinal microbiota, transcriptomics, and humoral immunity following symbiotic B. velezensis treatment.ResultsThe results revealed striking dynamic changes in the bacterial community composition of larvae in the treatment group at the genus level. Notably, Providencia and Morganella content increased, while Enterobacter content decreased, leading to inhibited larval growth. Moreover, the bacterial association with the larva significantly impacted the larval transcriptome, modulating the expression of genes involved in various biological pathways, including host growth and development, macronutrient metabolism, and energy production, which are essential for insect development and survival. Oral feeding of B. velezensis also caused significant morphological changes in the larval gut, resulting in notable larval mortality, cell degeneration, shrinkage, and the formation of various vacuoles. Additionally, we observed a significant decrease in immune response in housefly larvae, with a reduction in phenoloxidase activity and melanization ability in treated larvae compared to controls.DiscussionTherefore, B. velezensis can damage the vital functions of housefly larvae and may be utilized as a microecological regulator for the green prevention and control of housefly populations.